(untitled) (The International Research Journal of Management Science, 2021)
Background: Stock market experts analyse various indicators to estimate the stock market, including historical prices, economic analysis, industry analysis and company analysis, but this study uses historical prices for the NEPSE index, making forecasting more precise. Purpose: The purpose of this study is to explore short-term stock market momentum using fuzzy logic. The study also aims to establish a suitable fuzzy model to predict stock momentum, reduce the risk, and make the right investment decision. Methodology/Design: This study employed exploratory research design to understand the problem of chaotic decision making in the stock market. The mathematical method employed in this study is membership functions, which are part of fuzzy logic. This includes only the commercial banks, as it has the highest market capitalization, 53.11% of total market capitalization. Using 14-day past data as a base, the suggested fuzzy model determines the stock index’s momentum over the next 5 days. Findings: The forecasted trend value for the Nabil, Civil, and Prime Commercial bank is 0.92, 0.92, and 0.80, which shows a bullish trend. Compared to previously collected data, the findings closely reflect the expected real-world values.